Низкоскоростная торцевая электрическая машина бииндукторного типа - Булгар, Виктор Васильевич; Ивлев, Анатолий Дмитриевич; Ивлев, Дмитрий Анатольевич (НТУ "ХПИ", 2010)
Considered is the construction of low-speed end-rotor biinductor-type electric machine and, owing to the new design, providing a sufficient improvement of the number of unit indexes and the decreasing of the electrical power losses in static and dynamic moods of electrical drive.
Low-speed end-rotor biinductor-type electric machine
Keywords: электропривод; КПД; ротор